Analisis Faktor-Faktor yang Berhubungan dengan Kejadian Infeksi Nosokomial di RSUD Wonosari Tahun 2011 - Ika Puji Astuti; Purwanto Purwanto; Yamtana Yamtana (Sanitasi: Jurnal Kesehatan Lingkungan, 2012)
As the place for taking care of sick people, hospitals nonetheless can play as the source of in-fections, one of which is nosocomial infection that may lead to many disadvantages. This study was aimed to understand the description of nosocomial infection incidence in Wonosari General Hospital throughout 2011 by conducting an observational study with descriptive approach. The number of samples were 112 patients which were taken by followng exhaustive sampling me-thod. The results showed that the majority of cases had phlebitis, age group of 60-71 year was the biggest in number, yet female and male cases was equal. It was also revealed that most cases came with early diagnosis of neurological disorders and subsequently they were recorded using invasive devices, but had no comorbidity. Furthermore, it was also found that the majority of cases had been treated for more than 6 days and occupied class III ward for internal diseases care. Other results also showed that the nurses who taking care of the patients with good and mediocre behavior were equal in the percentage, and most of the cases were treated in clean rooms.